Juriprudence in Islamic Perspective: An Analysis of the General Rules of Fikih in Al-Qawāʻid Al-Fiqhiyyah Al-‘Āmmah against the Dynamics of Change - Herpraditya Sinar Panggalih; Shafratul Az-Zahra; Selly Agustina; Eka Suriansyah (Mir'ah: Family Law and Legal Culture, 2025)
The rules of fiqh, known as al-qawāʻid al-fiqhiyyah, are the basic principles of Islamic law that are made to facilitate the determination of the law on various issues in life. These rules are not only related to worship, but also muamalah and social life. The purpose of this study is to analyze the concept of fiqh rules as a whole, see the main principles in al-qawāʻid al-fiqhiyyah al-ʻāmmah, and see how fiqh rules develop over time. The research method used is normative method with descriptive analysis approach. Data were obtained from modern and classical literature, such as fiqh books and fatwas of scholars, using descriptive-analytical qualitative methods. The results show that Islamic law has the ability to adapt without losing its sharia principles, with rules such as “fatwas change according to changes in time, place, circumstances, intentions and customs” and “preserving the old that is beneficial and taking the new that is more beneficial”. Therefore, the principles of fiqh are still useful as a basis for dealing with legal challenges in the contemporary era.